A Reduced 2Fe2S Cluster Probe of Sulfur–Hydrogen versus Sulfur–Gold Interactions. Issue 38 (14th September 2015) - Crouthers, Danielle J.; Ding, Shengda; Denny, Jason A.; Bethel, Ryan D.; Hsieh, Chung‐Hung; Hall, Michael B.; Darensbourg, Marcetta Y.
Abstract The Ph3PAu+ cation, renowned as an isolobal analogue of H+, was found to serve as a proton surrogate and form a stable Au2Fe2 complex, [(μ‐SAuPPh3)2{Fe(CO)3}2], analogous to the highly reactive dihydrosulfide [(μ‐SH)2{Fe(CO)3}2]. Solid‐state X‐ray diffraction analysis found the two SAuPPh3 and SH bridges in anti configurations. VT NMR studies, supported by DFT computations, confirmed substantial barriers of approximately 25 kcal mol−1 to intramolecular interconversion between the three stereoisomers of [(μ‐SH)2{Fe(CO)3}2]. In contrast, the largely dative SAu bond in μ‐SAuPPh3 facilitates inversion at S and accounts for the facile equilibration of the SAuPPh3 units, with an energy barrier half that of the SH analogue. The reactivity of the gold‐protected sulfur atoms of [(μ‐SAuPPh3)2{Fe(CO)3}2] was accessed by release of the gold ligand with a strong acid to generate the [(μ‐SH)2{Fe(CO)3}2] precursor of the [FeFe]H2ase‐active‐site biomimetic [(μ2‐SCH2(NR)CH2S){Fe(CO)3}2].